Sosialisasi Pentingnya Kepemilikan Jaminan Kesehatan bagi Warga RT 37 Kelurahan Sidomulyo Kota Bengkulu - Susilo Wulan (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2022)
Background: community needs an assurance of availability of healthcare services and health financing, both from the goverment, companies and their own abilities through the health insurance mechanism. Membership of National Health Insurance (NHS) in RT 37 is 65,4%. So it is necessary to increase knowledg about the importance owning JKN Card. Purpose: Increasing awarness to participate in NHS and receive benefits from this participation through outreach activities so that communities understand the importance of owning JKN Card. Methods: the subject/target of the activity are resident of RT 37 Kelurahan Sidomulyo. Data collection technique used interviews and observtion, the analyzed to find out the root cause of problem. The results of the analysis are used to the basis for intervention such as Communication, Information and Education. Results: The root cause of the problem of owning JKN Card due to doesn’t sick don’t need JKN Card, inability to pay the premius for low income groups, not availabel data JKN Card membership in RT 37 and never received socialization from varias stake holders. Conclusion: Low of knowledge people in RT 37 so resident unknown the importance benefits of JKN Card Ownership, therefore proactive socialization needed from all stakeholders to attract people to became JKN membership.